Fundamentals Of Cyclone Gasification Process And Operation. - Miskam, M.A.; ldroas, M.Y.; Alauddin, Z.A.Z.; Mustafa, K.F.

(untitled)
Biomass refers to all organic materials that are originated from plants. Biomass is being traditionally used as energy source especially for cooking and heating particularly in the developing countries. Different biomass conversion processes produce heat, electricity and fuels. Among all biomass conversion processes, gasification is one of the promising ones.